Gasoline Alley shows PA program (Office of Public Relations, Duke University Medical Center, 1971)
Duke University Medical Center newsletter containing cartoon, photograph and article about Dick Moores publicizing physician's assistant programs in his comic strip, Gasoline Alley. The main characters in the comic strip, the Wallets, have a son, Chipper, who is 25, a Vietnam veteran, and former military corpsman, who is a prime candidate for PA education.